2015
DOI: 10.1002/msc.1108
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Delay in Rheumatoid Arthritis: A Qualitative Study of Symptom Interpretation Before the First Visit to the Doctor

Abstract: The nature and severity of symptoms are the deciding factors in their interpretation, by both the GP and the patient. Both the patient's disease recognition and his/her subsequent interaction with the doctor is influenced by the patient's body awareness and general attitude towards going to the doctor. The results showed that the greater the patient's body awareness, the better the disease recognition, the fewer barriers to contacting the GP and the shorter the delay in doing so. Copyright © 2015 John Wiley & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Previous qualitative studies and a meta-synthesis have identified barriers to help seeking at the onset of RA 37–43. The present study identifies that before seeking formal medical attention, people experiencing the early symptoms of RA seek information and help from a number of alternative sources and often self-medicate.…”
Section: Discussionmentioning
confidence: 78%
“…Previous qualitative studies and a meta-synthesis have identified barriers to help seeking at the onset of RA 37–43. The present study identifies that before seeking formal medical attention, people experiencing the early symptoms of RA seek information and help from a number of alternative sources and often self-medicate.…”
Section: Discussionmentioning
confidence: 78%
“…The start of many illnesses can, though, be difficult to recognise, and may sometimes only be appreciated in retrospect, once a diagnosis has been reached 10. Symptoms vary according to disease and some may be more easily recognised as pathological than others 11…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above findings, this present study demonstrated that COMP could be a useful laboratory marker for discriminating between patients with RA and healthy individuals, and it could also be used to judge the severity of the disease; findings that were in accordance with other research. 8 A previous study concluded that serum COMP was significantly higher in patients with RA compared with healthy subjects; and it was also significantly higher in patients with joint destruction compared with those patients in the early stages of the disease, but its levels were affected by age, disease duration, and body mass index. 29 In contrast, another study reported a sensitivity of 15%–48% and a specificity of 66%–69% for COMP as a marker for RA.…”
Section: Discussionmentioning
confidence: 96%
“… 6 , 7 These methods are often used to diagnose RA during the middle-to-late disease period when treatment is not able to effectively control the progressive articular and bone damage caused by the disease. 8 Research has confirmed that some biological markers reflecting cartilage degradation provide the possibility of early diagnosis. 7 Biomarkers may serve a wide range of purposes in clinical practice, but biomarker research must be the subject of a quantitative surrogate validation schema to ensure clinical and statistical validity.…”
Section: Introductionmentioning
confidence: 96%